PERANCANGAN BUKU MANFAAT BUAH DAN SAYUR PADA ANAK USIA 10-15 TAHUN - DHELLA ANDHIKA PRATIWI, Drs. Syafwan, M.Si., Ir. Drs. Heldi, M.Si., Ph,.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Mostechildren do not like fruits and vegetables because childreneprefer fast food and packaged drinks, due to the lack of print media that introduce the benefits of fruits and vegetables for children. The purpose of the design is to produce a book on the benefitseof fruits and vegetables in children aged 10-15 years in order to provide knowledge about the importance of the benefitseof fruits and vegetables and increase the desire of children to consume fruits and vegetables. This design uses visual communication design theory, print media theory, book theory, layout theory, illustration theory, and typographic theory. The design method uses theeglass box method, a research-based design, with a 5W + 1H analysis approach (what, who, where, when, why and how) to find solutions to the problems encountered. The design produces the main media of books about the benefits of fruits and vegetables in children aged 10-15 years and is also supported by several other media namely: e-books, posters, t-shirts, key chains, stickers, x-banners, and totabag as media support main and as a promotional media.Keywords: Books, benefits, fruits, vegetables